EYL's PERCEPTIONS ABOUT THE USE OF READING ALOUD TECHNIQUE FOR STUDENTS' COGNITIVE AND AFFECTIVE IN READING SKILL - Amanda Amanda; Maman Suryaman (Journal of English Educational Study (JEES), 2022)
One of the skills used to obtain information is reading skills. Reading is the first step and very important if you want to get a knowledge or information. Reading culture or literacy habits in Indonesia have a very low percentage compared to other countries. It will be more difficult if the student is learning a new language and has no interest whatsoever in reading. To overcome this, a technique is known to improve students' reading skills, especially in learning English. This study aims to determine the perception of EYL students in the use of reading aloud techniques for their reading skills in terms of cognitive and affective aspects. In addition, this study used narrative inquiry as a research design and data collection is carried out through interviews. The data were analyzed by categorizing and interpreting the data using Braun and Clarke’s theory. The results indicated that the students had positive responses based on their experiences using reading aloud technique in reading skill. For cognitive aspect, reading aloud technique improved students’s reading comprehension. Furthermore the data showed that for affective aspects, reading aloud technique increased students’ reading interest, improve students’ self-confidence and motivation to learn English better.Keywords: English Young learners (EYL), Reading Aloud Technique, Cognitive aspects, Affective aspects.